PdII-Catalyzed Cyclization of 1-Cyclopropyl-2-propynyl Acetates - Valentin Rautenstrauch (CHIMIA)
PdCl2(MeCN)2 catalyzes the cyclization of 1-cyclopropyl-2-propynyl acetates to 3-methyl-1,4-cyclopentadienyl acetates, which are cleaved in situ to 2-cyclopentenones.